2011
DOI: 10.1007/s00535-011-0464-0
|View full text |Cite
|
Sign up to set email alerts
|

Processed blood volume impacts clinical efficacy in patients with ulcerative colitis undergoing adsorptive depletion of myeloid lineage leucocytes

Abstract: GMA adjusted to patients' BW and at a vastly greater processed volume produces significantly higher efficacy as compared with the routine GMA protocol. Further, in this study, up to twofold higher processed volume caused no safety concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…The publication of the first clinical experience with GMA in patients with UC by Shimoyama, et al [31] generated significant interest in this non-pharmacological treatment intervention for patients with inflammatory diseases associated with activated myeloid lineage leucocytes [5-19,23-27,31-38]. However, as already mentioned, there is no shortage of contrasting efficacy outcome reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication of the first clinical experience with GMA in patients with UC by Shimoyama, et al [31] generated significant interest in this non-pharmacological treatment intervention for patients with inflammatory diseases associated with activated myeloid lineage leucocytes [5-19,23-27,31-38]. However, as already mentioned, there is no shortage of contrasting efficacy outcome reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment protocol might be inadequate as Sakuraba, et al [9] found that 2 GMA sessions per week produced significantly higher efficacy rate in a shorter time as compared with one session per week. Similarly, Yoshimura, et al [19] reported that more than 3000 mL of processed blood volume per GMA session was significantly more effective than routinely applied 1800 mL per session. Additionally, our experience suggests that unlike drug based medication, GMA demands operational skills, and maintenance of a steady blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Adacolumn, which is used for GMA is filled with carrier beads that interact with fragment crystallizable‐gamma receptor (FcγR) expressing leucocytes described below and tentatively presented in Figure . Patient's blood via a venepuncture in an antecubital vein enters the column and then back to the patient via the column outflow line.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yoshimura et al . reported that GMA could achieve a significant higher clinical efficacy by up to twofold higher processed volume (≥ 60 mL/kg) without any safety concerns 53 . We have to optimize the optimum Pv for GMA by adjusting Qt since Qb should be 30 mL/min because of its adsorption mechanism.…”
mentioning
confidence: 99%